Thermographic Mapping of the Melt Pool of the Laser Powder Bed Fusion Process - Jiři Sika; Vladimír Kindl; Michal Křížek; Tomáš Kavalíř; Michal Frivaldský (Communications, 2023)
The article describes an advanced test stand for measuring temperatures during the 3D printing for additive manufacturing. Based on mathematical procedures, it analyzes the impact energy of the laser beam used in metal 3D printing.